2014
DOI: 10.1007/s00266-014-0369-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors, Assessment, and Outcomes of Cosmetic Procedures: A Systematic Rapid Evidence Assessment

Abstract: Systematically reviewing this literature for UK policy has highlighted that some groups may be at risk of poor post-cosmetic procedure outcomes. Practitioners and patients must explore reasons for seeking cosmetic procedures and discuss all potential results and alternative solutions. Future research should employ more robust methodologies to identify effects in those at risk, led by consensus on a core set of psychological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…By improving the appearance of a person, facial cosmetic surgery, especially rhinoplasty, can improve the mental, emotional, and psychosocial functioning and well-being of that patient in the long term, by boosting self-confidence and self-esteem and even improving the professional life of the patient [4][5][6]. Different demographic, social, and psychological factors have been proposed as predictors for requesting cosmetic surgeries such as rhinoplasty [7]. However, the factors that affect the probability of seeking cosmetic surgery vary with the procedure, culture, and religion of a society [2].…”
Section: Introductionmentioning
confidence: 99%
“…By improving the appearance of a person, facial cosmetic surgery, especially rhinoplasty, can improve the mental, emotional, and psychosocial functioning and well-being of that patient in the long term, by boosting self-confidence and self-esteem and even improving the professional life of the patient [4][5][6]. Different demographic, social, and psychological factors have been proposed as predictors for requesting cosmetic surgeries such as rhinoplasty [7]. However, the factors that affect the probability of seeking cosmetic surgery vary with the procedure, culture, and religion of a society [2].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of cosmetic interventions on psychological outcomes are mixed; some findings indicated that satisfaction and self-esteem were positively associated with the minimally invasive cosmetic interventions, while in some studies no change in self-esteem was reported [14,15].…”
Section: Temperamentmentioning
confidence: 99%
“…There is a research gap between the number of studies that examined the influence of cosmetic surgery on selfesteem and body image satisfaction, and the number of papers that examined the correlation between minimally invasive procedures, self-esteem, and body image satisfaction [14]. Few studies examined the connection between temperament traits and cosmetic surgery, but, to the best of our knowledge, there are is no research about the relation between temperament traits and minimally invasive cosmetic procedures [12,13].…”
Section: Temperamentmentioning
confidence: 99%
“…Indeed, the imperative of improving methods of patient selection has been highlighted in a number of reports. 37,41,45,46 Reviews by Honigman et al 47 and Brunton et al, 36 together with prospective research by von Soest et al, 48 offers on procedures that a patient has not hitherto considered, 41,52 undue pressure to make quick decisions to undergo treatment through the use of incentives or discounts, 53 a cursory approach to patient assessment and selection (for example, by receptionists lacking the necessary expertise) 44 and aggressive marketing techniques, including the use of idealised and frequently digitally enhanced photographic images of 'clients', that promote false expectations of outcomes. 41,54 Evidence for the negative impacts on consumers of these types of business practices is mounting in the psychological literature.…”
Section: Education and Trainingmentioning
confidence: 99%
“…Brunton et al's 36 referral routes for more specialised assessment or support for clients whenever this is indicated.…”
Section: Implement Routine Audits and Contribute Data To Researchmentioning
confidence: 99%